Students’ Perspective on E-Learning Through Google Classroom For Teaching English at SMK Negeri 1 Parepare - Mutmainah, St; Salasiah, Salasiah; Sianna, Sianna (La Parole : Journal of Language Teaching and Pedagogy, 2021)
The learning program in schools has not been implemented for a long time. This was done to minimize physical contact or interaction between the teachers and students, to break the chain of transmission of Covid-19. Further, to fill teaching and learning activities that should be completed, the government adopted a policy through distance learning with online media. As for one of online media that is being used in learning, especially at SMKN 1 Parepare, that is by using the Google Classroom application. Therefore, this study was conducted to obtained students’ perspective on E-Learning through Google Classroom for teaching English. The researcher used qualitative design with case study method and used purposive sampling. To obtain the data, the researcher used three instruments, namely observation, interview, and documentation. After analyzing the data, the research result indicated students' perspectives on using Google Classroom for teaching English were not optimal during the Covid-19 pandemic.